1999
DOI: 10.2508/chikusan.70.201
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Pigeon Pea (Cajanus cajan L.) Seed Meal on Growth Performance in Piglets and Growing Pigs

Abstract: To investigate the effects of dietary pigeon pea (Cajanus cajan L.) seed meal (PM) on growth performance in early life stage of pigs and whether the raw PM could be used as a plant protein resource, 32 piglets were randomly allotted into 0, 10, 20 and 30% dietary PM groups of 8 pigs (2 pigs attained to the final 30kg body weight. Then, the composition of basal diet was changed from piglet diet to growing pig (30-60kg) diet. In both experimental feeding periods, feed intake, body weight gain, feeding period (da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…seeds have a great potential as an important protein source (Cheva-Isarakul, 1992;Oshodi et al, 1993) and every effort has been made to use pigeon pea seed meal (PM) for chickens (Mizubuti et al, 1995), pigs (Batterham et al, 1993;Mekbungwan et al, 1999) and lambs (Rao and Phillips, 2001). However, the efficacy of PM is limited by the presence of protease inhibitors such as trypsin and chymotrypsin inhibitors (Batterham et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…seeds have a great potential as an important protein source (Cheva-Isarakul, 1992;Oshodi et al, 1993) and every effort has been made to use pigeon pea seed meal (PM) for chickens (Mizubuti et al, 1995), pigs (Batterham et al, 1993;Mekbungwan et al, 1999) and lambs (Rao and Phillips, 2001). However, the efficacy of PM is limited by the presence of protease inhibitors such as trypsin and chymotrypsin inhibitors (Batterham et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Box 1240, Heitersheim D-79420, Germany), and their chemical composition was analyzed at the Department of Animal Technology, Maejo University, Thailand (Table 1, see Mekbungwan et al [20] for chemical composition, such as the essential amino acid content of PM and SM).…”
Section: Methodsmentioning
confidence: 99%
“…Although its use is limited by the higher content of anti-nutritional factors such as trypsin and chymotrypsin inhibitors than SM [2,34], Ene-Obong [7] has reported that such anti-nutritional factors do not cause problems in animals based on in vitro protein digestibility. In feeding experiments, PM could substitute SM in diets for pig based on growth performance [20]. However, a clear understanding of the nutrient digestibility in PM is still lacking.…”
mentioning
confidence: 99%
See 2 more Smart Citations